Correlation between corneal biomechanical properties, applanation tonometry and direct intracameral tonometry. Issue 5 (20th December 2011) - Yu, A-Yong; Duan, Su-Fang; Zhao, Yun-E; Li, Xing-Yu; Lu, Fan; Wang, Jianhua; Wang, Qin-Mei
Abstract : Aim: To investigate the correlation between corneal biomechanical properties, applanation tonometry and direct intracameral tonometry. Methods: Patients scheduled for phacoemulsification were enrolled in this prospective observer-masked study. Central corneal thickness (CCT) was obtained with ultrasound pachymetry. Corneal biomechanical properties including corneal hysteresis (CH) and corneal resistance factor (CRF) were measured with the ocular response analyser. Applanation intraocular pressure (IOP) (IOPappla) was measured in the supine position. Intracameral IOP (IOPintra) was measured with a pressure transducer connected to a cannula inserted into the anterior chamber. Results: Fifty-eight eyes of 58 patients were included. There was a significant difference between IOPappla and IOPintra (17.3±4.1 vs 13.8±4.7 mm Hg, p<0.001). CCT was significantly correlated with CH and CRF (p<0.01). Univariate regression analysis revealed IOPappla was significantly correlated with CCT and CRF (p<0.05). IOPintra had no significant association with the corneal properties (p>0.05). Multivariate regression analysis revealed IOPappla=10.43+2.69CRF–1.99CH (p<0.001) and the difference between IOPappla and IOPintra (ΔIOP)=−1.57+0.55CRF (p=0.032). Conclusion: The mean difference between IOPappla and IOPintra was 3.5 mm Hg. While IOPappla was correlated with the corneal biomechanical properties of CH and CRF, IOPintra was not. IOPappla was correlated more with the corneal biomechanical properties assessed by the ocular response analyser than with CCT alone.